Morphology Process and Categorization of Village Names in Warunggunung District Lebak Regency Banten Province - Sulis Sulastri; Asep Muhyidin; Ilmi Solihat (CV. Tripe Konsultan, 2023)
The writing is the names of villages in the Warunggunung district, Lebak Regency, Banten Province. This research aims to describe the morphology, toponym categorization and meaning of village names in Warunggunung district. The research is a descriptive qualitative method with interview and observation techniques in the form of recording and note techniques. The results of the study show that; 1) The names of villages in the Warunggunung district beginning of word pasir and ci- based on their shape were formed through a composition process as many 37 village name starting with ci-. Formed through the abbreviaton process as many as 14 village names;and 2) The toponym category of the village in Warunggunung district consists of (1) embodiment aspect, 44 village names: (a) waters, (b) appearance of the earth, (c) natural environment of flora, fauna, and abiotik (d) flora and appearance of the earth (e) waters and appearance (f) waters and building, (2) community aspect, 2 village names, (a) community leaders (b) community activitaes, and (3) cultural asapect, 5 village names: (a) foklore (b) traditional musical instrument and (c) belief.